Catheter ablation of ventricular tachycardia associated with structural heart disease: Current status and perspectives. Issue 1 (January 2023) - Nakahara, Shiro
Abstract: Catheter ablation is an effective and safe treatment for ventricular tachycardia attributable to structural heart disease, reducing the risk of recurrent arrhythmias and defibrillator shock therapy. Advances in medical technology and an accumulation of data have led to the development of detailed guidelines. Successful ablation requires accurate identification of the arrhythmia substrate and effective delivery of radiofrequency energy to the target tissue. Modern practice requires use of traditional electrophysiological mapping processes such as entrainment mapping and three-dimensional activation sequence mapping in combination with newer functional mapping techniques for which there is growing support. Thorough non-invasive preoperative assessment is also necessary before an invasive procedure is undertaken. In this review, we summarize contemporary practice and recent randomized controlled trials underpinning the latest developments in mapping and ablation and discuss potential future developments in this field. Graphical abstract: Unlabelled Image Highlights: Catheter ablation is a safe and effective therapy that can reduce recurrent scar-related ventricular tachycardia (VT). New physiological mapping techniques are being used increasingly to complement traditional entrainment mapping techniques. Early VT detection, along with early treatment by catheter ablation, has effectively reduced recurrent VT and hospitalizations. VT ablation is a rapidly developing field that is likely to change the therapeutic landscape in the upcoming years. In addition, such ablation is likely to improve the life expectancy of patients with severe structural heart disease.